Assessing the Energy Metabolism of Urban Systems: A Comparison of Napoli and Hong Kong Through the MuSIASEM Approach - Rallo, Renato F.; Zucaro, Amalia (Journal of Environmental Accounting and Management, 2026)
Urbanization, that is the expansion of cities and the emptying of the countryside, has been the trend of the last decades and does not seem to stop. In light of this phenomenon, quantitatively analyzing cities through shared and standardized methods has become a scientific urgency. Nevertheless, the efforts made so far have proved to be insufficient, and a science of cities is still far from being constituted. In this paper we present a first attempt to evaluate the energy metabolism of Napoli and Hong Kong through the Multi-Scale Integrated Analysis of Societal and EcosystemMetabolism (MuSIASEM) and its End-Use Matrix, that is connecting produced and consumed flows to their users. The comparative analysis provides interesting results and potentially allows for useful policy recommendations.